2001
DOI: 10.1097/00001756-200105250-00048
|View full text |Cite
|
Sign up to set email alerts
|

Functional recovery after brain lesion???contralateral neuromodulation: an fMRI study

Abstract: Behavioral recovery takes place even after permanent damage to the entire brain region normally controlling sensorimotor hind limb function in the rat. In our study, 2 weeks after full behavioral recovery from an experimental unilateral permanent brain damage, the topographic representation of the previous paretic hindlimb was investigated by fMRI. The analysis showed that during electrical stimulation of the previously paretic hindlimb, two normally inactive brain regions were now being activated. One region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 20 publications
5
62
1
1
Order By: Relevance
“…Comparison with previous studies of plasticity after stroke In patients (Rossini et al, 2007) and animal stroke models (Abo et al, 2001;Dijkhuizen et al, 2001Dijkhuizen et al, , 2003Wei et al, 2001;Zepeda et al, 2003Zepeda et al, , 2004, ipsilesional regional reorganization as observed here is correlated with improved behavioral recovery. In rats with small infarcts, activity within the stroke-affected cortex was required for reaching task performance (Biernaskie et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…Comparison with previous studies of plasticity after stroke In patients (Rossini et al, 2007) and animal stroke models (Abo et al, 2001;Dijkhuizen et al, 2001Dijkhuizen et al, , 2003Wei et al, 2001;Zepeda et al, 2003Zepeda et al, , 2004, ipsilesional regional reorganization as observed here is correlated with improved behavioral recovery. In rats with small infarcts, activity within the stroke-affected cortex was required for reaching task performance (Biernaskie et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…4 The functional recovery includes some mechanisms, such as neo-formation of brain vessel, increase in axonal sprouting, development of new dendrites, and functional reorganization through recruitment of new brain regions, and neuromodulation to the opposite hemisphere. 5 Recently, brain function restoration after brain damage has also been related to changes in the dopaminergic neurotransmission system after cerebral ischemia in rats. 6 Likewise, clinical studies have shown that the use of pharmacological therapies that increase brain concentrations of brain amines such as dopamine and serotonin promotes a positive impact on stroke outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…2 The prepared suspensions of coated magnetic nanoparticles have recently been the focus of intensive research not only for the study of the physics of magnetism in the nanometer scale, 3 but also for the use of ferrofluids in many technological and biomedical applications such as technical heating processes, media contrast agents in magnetic resonance imaging ͑MRI͒, and as therapeutic agents for RF-magnetic hyperthermia. [4][5][6][7][8][9][10][11][12][13] Specifically, MRI contrast agents are chemical substances introduced to the anatomical or functional region being imaged, in order to increase the differences between different tissues or between normal and abnormal tissue, by altering the relaxation times. MRI contrast agents are classified according to the different changes in relaxation times after their injection.…”
Section: Introductionmentioning
confidence: 99%